Development of a proof of principle for universal neutralization of antibiotics in cord blood by‐products used for sterility testing. Issue 6 (7th March 2018) - Kou, Yuntong; Halpenny, Mike; Elmoazzen, Heidi; Ramirez‐Arcos, Sandra
Abstract : BACKGROUND: Bacterial contamination of cord blood (CB) represents a safety risk for transplantation patients. CB sterility testing at Canadian Blood Services' Cord Blood Bank is performed using a 1:1 mix of CB‐derived plasma and red blood cells (RBCs). Culture bottles of an automated culture system, which lack antimicrobial neutralization properties, are used for bacterial screening of CB. This process is unsuitable for CB‐containing antibiotics, potentially resulting in false‐negative results. This study was aimed at developing a protocol for antibiotic neutralization in CB used for sterility testing. STUDY DESIGN AND METHODS: Phase 1: four neutralizers—penicillinase, ion exchange resins L and A, lecithin + Tween80, and activated charcoal (AC)—were individually tested to neutralize penicillin or gentamicin in cultures of Staphylococcus epidermidis or Klebsiella pneumoniae, respectively, adjusted to 100 colony forming units/mL, in Müller‐Hinton broth (MHB). Phase 2: combinations of penicillinase plus resin L or penicillinase plus AC were assayed for the simultaneous neutralization of both antibiotics in MHB. Phase 3: penicillinase plus resin L was used to neutralize both antibiotics in CB sterility testing samples (plasma + RBCs). RESULTS: Phase 1: penicillin was neutralized by penicillinase and resin A, while gentamicin was neutralized by resin L and AC. Phase 2: the antibiotics were simultaneously neutralized by the two neutralizer combinations tested. Phase 3: neutralization of both antibiotics in CB was achieved with penicillinase and resin L. CONCLUSION: A protocol for antibiotic neutralization in CB sterility testing samples has been successfully developed at Canadian Blood Services' Cord Blood bank. This in‐house assay applies to any culture‐based CB bacterial screening method.